Straight lane saturation flow and its rate in Serbian cities - Stanić, Branimir; Tubić, Vladan; Čelar, Nikola (Transport, 2011)
Saturation flow is the base rate in the procedure for optimizing traffic signal operation and determining the measure for effectiveness of intersection operation. Different approaches and structures of analytical value models indicate the complexity of the problem of determining the saturation flow value in real conditions. This paper presents the synthesis of the results and conclusions of studying the saturation flow rate phenomenon at signalised intersections in Serbia in the last thirty years, by applying various survey techniques. The surveys relate to straight lane saturation flow value, in the survey conditions mostly resembling the idealised conditions in which saturation flow can be generated. The obtained results indicate that there is a significant trend of changes in the base saturation flow value compared with those first referred in 1963 by Webster and Cobbe, change in the significance of impact factor on saturation flow value, and the necessity to determine them on the local level.First Published Online: 05 Oct 2011